Impact assessment of a wind turbine blade root during an offshore mating process. (1st February 2019) - Verma, Amrit Shankar; Jiang, Zhiyu; Vedvik, Nils Petter; Gao, Zhen; Ren, Zhengru
Highlights: Impact between the blade root and hub during an offshore mating task is studied. The sideways impact between the guiding connection and hub is found critical. Impact load causes severe bending and plastic deformation of the guide pin bolt. Excessive bending of guide pin triggers the failure of the adjacent root laminate. Guidelines are provided to aid onboard decision making after the impact events. The study aims to derive response-based operational limits for the mating task. Abstract: Single-blade installation is a popular method for installing blades on bottom-fixed offshore wind turbines. A jack-up crane vessel is often employed, and individual blades with their roots equipped with mechanical joints and bolted connections are lifted to the tower-top height and mated with a pre-assembled hub. The final mating phase is challenging and faces significant risks of impact. Due to relative motions between the blade and the hub, substantial impact forces may arise and lead to severe structural damages at root connections, thereby causing delays in the installation task. The present paper considers a realistic scenario of the mating process and investigates the consequences of such impact loads. Here, a single-blade model with tugger lines and a monopile model were established using a multi-body formulation, and relative velocities under collinear wave and wind conditions were obtained. A three-dimensional finite element model was developed for the blade root with T-bolt connections, and an impact investigation was performed for the case in which a guiding connection impacts the hub. The results show severe bending and plastic deformation of the guide pin bolt together with failure of the adjoining composite laminate at the root connection. Based on the type of damage obtained for the different environmental conditions considered, this paper also discusses its consequence on the installation tasks and suggests onboard decision making in case of an impact incident. The results of this study provide new insights regarding the mating phase and can be utilised to establish response-based operational limits.